Countering the “Kingsclear blunder”: Maliseet Resistance to the Kingsclear Relocation Plan, 1945-1949 - Walls, Martha (Acadiensis, 2008)
Abstract In the 1940s the federal government undertook schemes to relocate Native people in the Maritimes from smaller reserves to centralized settlements. Beginning in 1945 New Brunswick’s Maliseet were targeted with centralization, as Ottawa planned to relocate the people of the St. Mary’s, Woodstock, and Oromocto reserves to Kingsclear, northwest of Fredericton. New Brunswick centralization, however, failed in large part due to the actions of the Maliseet. By denouncing centralization publicly, by petitioning federal officials, and by reconstituting a Saint John River Valley Maliseet political collective, the Maliseet successfully stymied Ottawa’s New Brunswick centralization plan.